Percepatan Penyembuhan Luka oleh Krim Ikan Gabus (Ophiocephalus striatus) terhadap Luka Kulit Kelinci secara Histopatologi - ROBERT TUNGADI; FAISAL ATTAMIMI; EVA FIRMINA SABU; EKO NUGRAHA (Fakultas Farmasi Universitas Pancasila, 2011)
The aims of the study were to investigate the effect of cream containing various concentrations of snakehead fish on the duration of wound recovery and skin histology as compared to control. Samples of the study were nine rabbits divided into three groups for treatment, i.e. group I (0.5%), group II (1%), and group III (2%). Each rabbit in each group was wounded with scalpel as wide as 4 cm2 on the left and right dorsal thigh. Wound on the left dorsal was applied with snakehead fish cream (accordingly to each concentration) and the right dorsal with basic cream as control. The observations were carried out on day 3, day 6 and day 12 by measuring the wound size and taking picture of the wounded area. On the day 12, skin incision were performed on each group to observe histopathology. The data were analyzed statistically by the SPSS 15 program of repeated measures test. The results indicated that group III (2%) had significant effect on wound recovery by decreasing the wound size every day (p < 0.05). The results were confirmed by observing the skin histopathology, indicating that cream containing 2% snakehead fish could faster improve the tissue granulation as compared to the 0,5% and 1% concentration. It can be concluded that the application of 2% snakehead fish cream for 12 days can accelerate the wound recovery.